2009
DOI: 10.1111/j.1365-2966.2009.15230.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dark matter substructures on gravitational lensing: results from the Aquarius simulations

Abstract: We use the high-resolution Aquarius simulations of the formation of Milky Way-sized haloes in the cold dark matter cosmology to study the effects of dark matter substructures on gravitational lensing. Each halo is resolved with ∼10 8 particles (at a mass resolution m p ∼ 10 3 to 10 4 h −1 M ) within its virial radius. Subhaloes with masses m sub 10 5 h −1 M are well resolved, an improvement of at least two orders of magnitude over previous lensing studies. We incorporate a baryonic component modelled as a Hern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
113
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 116 publications
4
113
1
Order By: Relevance
“…The predicted fraction of substructure from simulations within the same mass range and projected distance from the host halo centre is ∼ 0.1 +0.3 −0.1 % (ref. 19), which is marginally smaller than the lower limit implied by our detection of a substructure at the 68 per cent confidence level, independent of the prior set on the slope of the mass function. However, these simulations model the formation of a Milky Way halo at z = 0 and simulations of elliptical galaxies out to z ∼ 1 must be made before a more quantitative conclusion can be drawn.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…The predicted fraction of substructure from simulations within the same mass range and projected distance from the host halo centre is ∼ 0.1 +0.3 −0.1 % (ref. 19), which is marginally smaller than the lower limit implied by our detection of a substructure at the 68 per cent confidence level, independent of the prior set on the slope of the mass function. However, these simulations model the formation of a Milky Way halo at z = 0 and simulations of elliptical galaxies out to z ∼ 1 must be made before a more quantitative conclusion can be drawn.…”
contrasting
confidence: 55%
“…Hence, the shape of the substructure mass function cannot be constrained and so far it has remained unclear whether the results from quasar flux ratio anomalies are in agreement or disagreement with numerical simulations 19 . Our new low-mass detection also allows us to constrain for the first time the slope of the substructure mass function for galaxies other than our own, when combined with the detection of the ∼18-fold more massive (i.e.…”
mentioning
confidence: 99%
“…Dalal & Kochanek 2002;Bradač et al 2004;Dobler & Keeton 2006;Metcalf & Amara 2012) suggest consistency between the CDM model and observations, others (e.g. Mao et al 2004;Amara et al 2006;Macciò & Miranda 2006;Chen, Koushiappas & Zentner 2011) including those by us (Xu et al 2009(Xu et al , 2010 find that subhaloes from CDM simulations are actually insufficient to explain the observed radio flux-anomaly frequency.…”
mentioning
confidence: 98%
“…For example, as shown by Keeton, Gaudi & Petters (2003), flux ratios are quite sensitive to the ellipticity of the main lens. Metcalf & Amara (2012) also pointed out that one of the reasons that our previous studies (Xu et al 2009(Xu et al , 2010 did not reproduce enough perturbations to match observations could be due to our adoption of a restricted ellipticity instead of the full range of ellipticities in the main lens models.…”
mentioning
confidence: 99%
“…Xu et al 2009Xu et al , 2015. For example, Hsueh et al (2015) have shown that the flux ratio anomaly of CLASS B1555+375, one of the most anomalous lens systems known, can be explained by the presence of a previously undetected edge-on disc in the lens galaxy.…”
Section: Introductionmentioning
confidence: 99%